Neutrophil‐mediated oxidation of erythrocyte peroxiredoxin 2 as a potential marker of oxidative stress in inflammation. Issue 8 (19th April 2013) - Bayer, Simone B.; Maghzal, Ghassan; Stocker, Roland; Hampton, Mark B.; Winterbourn, Christine C.
Abstract : Peroxiredoxin 2 (Prx2) is an abundant thiol protein in erythrocytes. It is oxidized readily on exposure to hydrogen peroxide (H2 O2 ) and provides antioxidant protection by cycling between its reduced and disulfide‐bonded forms. To test whether Prx2 oxidation could occur in pathological situations where neutrophils are activated, we exposed human erythrocytes to stimulated neutrophils and measured Prx2 oxidation by immunoblotting of nonreducing gels. With phorbol myristate acetate, lipopolysaccharide or Staphylococcus aureus Prx2 dimer increased from <5% to up to 100% depending on neutrophil number and incubation time. Studies with inhibitors and myeloperoxidase‐deficient neutrophils showed that H2 O2 generated by the neutrophil NADPH oxidase was responsible. Prx2 oxidation was detected at erythrocyte:neutrophil ratios found in blood and reversed over time as the oxidative burst subsided. Acidotic conditions also increased erythrocyte Prx2 oxidation. In a mouse model of endotoxemia induced by lipopolysaccharide, oxidized Prx2 increased transiently from <1 to 15%, then reverted to baseline by 24 h. No increase was seen in mice lacking NADPH oxidase activity. These results indicate that erythrocyte Prx2 scavenges H2 O2 produced during inflammation. Oxidized erythrocyte Prx2 could be a sensitive real‐time marker of systemic neutrophil activation and an early indicator of inflammation and oxidative stress.—Bayer, S.B., Maghzal, G., Stocker, R., Hampton, M.B., Winterbourn, C.C. Neutrophil‐mediated oxidation of erythrocyte peroxiredoxin 2 as a potential marker of oxidative stress in inflammation. FASEBJ. 27, 3315‐3322 (2013). www.fasebj.org